Studying and Analyzing Operating Conditions of Hollow Fiber Membrane Preparation Process - Zaid Rashad (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Polymeric hollow fiber membrane is produced by a physical process called wet or dry/wet phase inversion; a technique includes many steps and depends on different factors (starting from selecting materials, end with post-treatment of hollow fiber membrane locally manufactured). This review highlights the most significant factors that affect and control the characterization and structure of ultrafiltration hollow fiber membranes used in different applications.